Effect of Long time Feeding of Cotton seed cake (Gossypum sp.) on Blood profile, Testicular biometry and Semen attributes in growing Barbari Goats - Kumar, Ravindra; Gangwar, Chetna; Swaroop, Kamendra (Indian Journal of Animal Nutrition, 2022)
Long time (319 days) feeding trial was organized in eighteen male growing Barbari goats (Age approx. 5m and mean BW 10.37 Â± 0.19Kg). Animals were distributed into three groups (Gr I, Gr II and Gr III) of six each as per completely randomized design and were fed with concentrate pellet and Bengal gram (Cicer arietinum) straw to meet their nutrient requirement. Gr I was fed with concentrate pellet (having linseed (Linum usitatissimum) cake as protein source), while Gr II and Gr III was fed with T1 (having equal proportion of linseed and cotton seed (Gossypum sp.) cake as protein source) and T2 (having cotton seed (Gossypum sp.) cake as protein source) concentrate pellet respectively. Testicular biometry was measured at 9 and 12 months of age. Blood was collected at the end of experimental feeding and semen was collected around 13 months of age. No statistically (P>0.05) significant difference was reported in testicular breadth and circumference between different groups of goats. Hematology and different blood metabolites were similar in all three groups of goats. 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Super oxide dismutase (SOD) activity was also statistically similar (P>0.05) in all three groups of goats.Â Testosterone (ng/ml) was 11.97 for Gr I, 12.17 for Gr II and 11.96. No statistically significant (P<0.05) was reported in the serum testosterone level in different group of goats. The colour of semen from Gr I was Creamy yellowish while in other groups (Gr II and Gr III) it was creamy. Gossypol feeding had no detrimental effect on consistency, mass motility, progressive motility and viability of sperm in Gr II and Gr III. Malondialdehyde (MDA) in seminal plasma was significantly (P<0.05) increased by feeding of cotton seed cake. The study inferred that long time feeding of Cottonseed cake (Gossypum sp.) had no deleterious effect on blood and semen attributes in goats.